Gaya keibubapaan ibu tunggal dalam perkembangan sosioemosi remaja: kajian kes di Tanasitolo, Indonesia - Hamzah, Ika Indrawaty (2020)
Single mother problems are a complex issue because their parenting style can have an impact on adolescent's socioemotional development. Although there are many studies on the parenting styles, single mothers' parenting style has not been much explored. Therefore, a qualitative case study was conducted to illustrate the types of single mothers parenting styles, understand the factors contributing to single mothers parenting style, understand parenting style in terms of social skills and adolescent empathy, and explore social support to resolve issues faced by single mothers in adopting their parenting style towards adolescent's socioemotional development. The study utilized interview method, observation, and documentary evidence with eighteen participants consisting of single mothers, adolescents, classroom teachers, and Counselling teachers. The data were analyzed using thematic analysis software NVivo 11. The study showed that single mothers practiced both types of authoritative and authoritarian parenting styles. Single mothers authoritative styles are practiced by communication through motivation and guidance, open discussion, and love. They are always in control of the rules and support the activities of their children. However, in certain cases single mothers are authoritative by being strict and limiting their autonomy by disciplining their children, limiting communication, overprotecting, and not supporting their child's activities. Besides, there are three factors contributing to the practice of single mothers parenting style such as low socioeconomic, psychological, and number of children. It is found that single mothers parenting style has successfully developed the aspects of social skills and adolescent's empathy. In addition, single mothers receive support from family, friends, and the government to address the problems they faced. This study empirically supports human ecological development, attachment, and psychosocial development theories. Practically, the findings of this study contribute to the policy makers in designing programs/courses to address the single mothers phenomena in order to improve parenting quality and personal skills